The condominium status of Ukrainian lands in the 14th century: from the first territorial acquisitions of Poland and Lithuania under the rule of the Golden Horde to Mamai’s yarlyk - Shabuldo, Feliks M. (Balcanica Posnaniensia. Acta et studia, 2007)
The issue of the status of Ukrainian lands in the 14th century (comparable to a condominium) has not been sufficiently researched by historians. The significance of this issue lies in the fact that it reflects important revaluations in political and socio-economic relations between nomadic and settled populations in Eastern Europe in the late Middle Ages. The aim of this article is to determine the nature of the subordination of Ukrainian lands (Halych-Volhynia, the Duchy of Kyiv and Podolia) to the dominant powers in the region in the 14th century – Poland, Lithuania and the Golden Horde. Based on a comparative analysis of sources: chronicles, diplomatic documents, decrees of the khans of the Golden Horde and Crimea, and numismatic materials, the author describes the status of Ukrainian lands as temporary. A key indicator of this status was the regular payment of tributes to the khans, which, however, corresponded to the gradual weakening of Tatar rule.